Transporte, modernización urbana y negociación: el Ferrocarril Urbano de Santiago 1873-1897 - Elisabet Prudant Soto (Les Cahiers ALHIM)
This text analyses the importance of the Urban Railway of Santiago as a participant actor in the production of the urban space and as a facilitator device of the mobility at the capital of Chile between the years of 1873 and 1897. This analyses the expansion's phases of its trace and the gradual ramification of the routes to the urban and suburban periphery; as well as the main conflicts faced by the Company that was administered the service, maintained with the Municipality and with the users. The years that frame this work refer to the scene starred by a mean of transport that impacted early in the city's configuration at the moment of establish the routes of circulation that connected principal points with farther and devalued lands by the fault of services. It is about a significant phase, as it represents the first experience of advanced of collective means of transport in Santiago. The urban Railway contributed with the material basis on which will concretize the overcrowding of the use of the tram, made viable since the year of 1900 by the introduction of the electrical traction. The closing date of the research coincides with the decline of the Company that monopolized the service of transport on rails in Santiago and with the entry of transnational capitals to the industry of the urban mobility in Chile.